(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
A field experiment was conducted at the Botanical Garden of Biological Science Department, Ibrahim Badamasi Babangida University during the 2023 cropping season to investigate the influence of different composted plant materials on growth and yield of bell pepper. The three plant materials used were Moringa oleifera fruits, neem fruits and locust beans fruits which were collected and composted. The composted materials were applied each at the rate of 0, 10, 20 and 30kg corresponding to 0, 10, 20 and 30t/ha respectively. These treatments were arranged in a completely randomized block design (RCBD) in three replications. Bell pepper growth and yield attributes measured included plant height, stem girth, number of leaves per plant, leaf area, length of branches, number of flowers per plant (NOFL/PLT), number of fruits per plant (NOF/PLT), fruit diameter (FDM) and fruit weight per plot (FW/PLOT). Data collected on all the mentioned parameters were subjected to analysis of variance (ANOVA) using Minitab statistical software version 2017. Means that showed significant differences were separated using Tukey Pairwise Comparison at 5% probability level. Results from the ANOVA indicated that composted plant material (CPM) produced a significant effect on plant height, stem girth, leaf area, number of leaves per plant and length of branches with composted locust beans fruits showing superiority in growth attributes of pepper compared to Moringa oleifera and neem fruits. Composted neem fruits consistently recorded the least effect on all the growth and yield parameters of bell pepper evaluated. It was also observed to produce...